Reducing wrinkling and tearing of deep draw part - Mohd Naeemil Mahmudi, Mahmud (2012)
Some of the most common outcomes in deep drawing process are tearing and wrinkling or the formation of uneven height at the top rim of a drawn part due to the material anisotropy. This project involves experimental and numerical studies of the die design to investigate the formability of sheet metal. The main objective of this project is to obtain the best deep drawing parameters in reducing wrinkle and tearing during a cylindrical cup deep draw process. The project begins with the die design using Computer Aided Design (CAD) software. The project is continued with modelling of finite element model (FEM) using simulation software. The variables for this project are die clearance, die radius, and blank holding force. The constant of this simulation are thickness of sheet metal and punch size to deform the material. All the data from finite element software showed the different value of displacement. From the data documentation, the discussion and result were concluded to determine the effect of different parameters on wrinkling and tearing phenomenon during sheet metal forming process.